Country-Specific Roadmaps for Scaling Up Integrated Care in Belgium, Slovenia, and Cambodia – Lessons Learned from the SCUBY Project - Martin Heine; Monika Martens; Daniel Boateng; Grace Marie Ku; Roy Remmen; Edwin Wouters; Srean Chhim; Por Ir; Antonjia Poplas Susič; Wim van Damme; Josefien van Olmen; Kerstin Klipstein-Grobusch; et al. (International Journal of Integrated Care)
Introduction: The SCUBY project aimed to provide knowledge on the scaling-up of an Integrated Care Package (ICP) for type 2 diabetes and hypertension across three distinct health systems (Cambodia, Slovenia, and Belgium). Here, we analyse the different elements of the country-specific scale-up roadmaps to identify similarities and differences, and share lessons learned. Methods: Thematic analysis was used to derive crucial roadmap elements from key SCUBY documents (n = 20), including policy briefs, interim reports, research outputs, and consortium meeting notes. Results: Roadmap elements differed according to priority needs, features of the (health) systems, and partly reflected the position of the SCUBY research team within each country. Common cross-country elements were: task-shifting to patients themselves, nurses and community health workers; strengthening monitoring and evaluation; and creating an enabling environment for ICP implementation. Discussion: Scale-up of complex interventions requires continuous engagement of multiple stakeholders and contextualization of action plans. The linkage of research teams with key implementation stakeholders and policy makers creates change-teams, allowing advancement from formative research to implementation of roadmap strategies and full scale-up in due time. Conclusion: The development processes and contents of the roadmaps provided essential and reciprocal learnings. These learnings help shape future policy dialogues and best practices to tackle chronic disease in each participating country.